2017
DOI: 10.1007/s40264-017-0564-8
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Adverse Drug Reactions Associated with Proton Pump Inhibitors: A Disproportionality Analysis Using the Italian National Network of Pharmacovigilance Database

Abstract: This explorative study suggests that the class of PPIs could be involved in reports of muscular ADRs, rather than any other ADR, more frequently than any non-statin drug. Our results must be corroborated by further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 83 publications
3
15
0
Order By: Relevance
“…Several studies have reported an association between myopathy and use of a PPI, and some mention an association between rhabdomyolysis and PPIs. [5][6][7]17 However, these reports are based on analyses of small numbers of patients with rhabdomyolysis. Various theories have been put forward to explain the mechanism of the muscle injury caused by PPIs, including induction of autoimmune antibodies, non-autoimmune antibody-mediated hypersensitivity reactions, electrolyte disorders, and autophagic myopathies, and it seems likely that all these mechanisms have an effect on muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported an association between myopathy and use of a PPI, and some mention an association between rhabdomyolysis and PPIs. [5][6][7]17 However, these reports are based on analyses of small numbers of patients with rhabdomyolysis. Various theories have been put forward to explain the mechanism of the muscle injury caused by PPIs, including induction of autoimmune antibodies, non-autoimmune antibody-mediated hypersensitivity reactions, electrolyte disorders, and autophagic myopathies, and it seems likely that all these mechanisms have an effect on muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, PPIs are known to increase the risk of various adverse events, including nephropathy, gastrointestinal infection, pneumonia, and fractures, which in turn increase the mortality risk. 3,4 According to several studies, [5][6][7] one of the severe adverse events caused by PPIs is myopathy. Although the mechanism of PPI-induced muscle injury is still unclear, various mechanisms have been suggested, including induction of autoimmune antibodies or electrolyte disorders as a result of long-term PPI use.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sansone et al . surveyed the Italian National Network of Pharmacovigilance Database and found that omeprazole was more frequently involved in reports of myopathy than any other nonstatin drugs . From this evidences omeprazole is the primary candidate that induced myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that long term use of PPIs can result in polymyositis, a type of chronic inflammation in the muscles [40]. Another possible, but rare side-effect of PPI use is rhabdomyolysis, a condition in which damaged muscle breaks down rapidly, and the breakdown product can effect kidney function [41,42]. To conclude, although generally considered safe, long-term use of PPIs could ultimately lead to deficiencies in several vitamins and minerals [36,37,43].…”
Section: Adverse Effects Of Long Term Use Of Ppismentioning
confidence: 99%